2020
DOI: 10.1017/jfm.2020.758
|View full text |Cite
|
Sign up to set email alerts
|

Flapping of heavy inverted flags: a fluid-elastic instability

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…This phenomenon was also observed in the experimental study of Tavallaeinejad et al. (2020 c ), which suggests that momentum-induced aerodynamic forces govern the periodic fluttering motion. Also, it has been shown that inverted flags undergo self-sustained periodic fluttering for a wide range of , defined here as the width to length ratio (Sader et al.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…This phenomenon was also observed in the experimental study of Tavallaeinejad et al. (2020 c ), which suggests that momentum-induced aerodynamic forces govern the periodic fluttering motion. Also, it has been shown that inverted flags undergo self-sustained periodic fluttering for a wide range of , defined here as the width to length ratio (Sader et al.…”
Section: Introductionsupporting
confidence: 72%
“…The motion of heavy flags with strong inertial forces compared with fluid dynamic forces is governed by fluid elastic instability (Tavallaeinejad et al. 2020 c ), wherein the changes in the geometry and the flow forces are in a dynamically balanced state to promote continuous fluttering motion. We discuss the connection between the deformation-induced vortical structures and fluttering dynamics in the bistable response range by visualizing the Q-criterion (Q), at and , as shown in figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, at the highest value of U * = 18.4, the tip oscillations become chaotic, as seen in Figure 11c, while the predominant frequency of vibration becomes almost equal to the structural frequency of the plate, i.e., f ≈ f n . This could indicate that the vibration resembles flutter, i.e., fluid-elastic instability associated with relatively large amplitude oscillations at the structural frequency beyond some critical reduced velocity [59]. It will be very interesting to examine the plate response in more detail in the range of 11.1 < U * < 18.4, which corresponds to the transition between synchronized vortex-induced vibration and chaotic-like flutter vibration, in future work.…”
Section: Discussionmentioning
confidence: 99%
“…However, the position of VIV as a governing phenomenon has been challenged in recent work from Tavallaeinejad et al. (2020 a , b ). These authors argue that, at least for heavy flags, the mechanism is not VIV but is instead related to coupled-mode flutter-like instabilities, or a movement-induced excitation (Naudascher & Rockwell 1994; Païdoussis 2014, 2016).…”
Section: Introductionmentioning
confidence: 99%